Weight Median Filter Using Neural Network for Reducing Impulse Noise - Hasoon, Feras N. (2004)
Noise is undesired information that affects an image. Noise appears in images from various sources. Noise reduction and noise removal is an important task in images processing. The weight median filters are extension of the median filter; it belongs to the broad class of nonlinear filters. Weight median filter is more effective form of image processing, it is the removing ability of impulsive noise. Impulsive noise is a kind of image corruption where each pixel value is replaced with an extremely large or small value that is not related to the surrounding pixel values by a probability. iv The design of weight coefficients of the weight median filter is considered as a difficult problem. The weight coefficients of the weight median filter learnt by the backpropagation with supervised multi-layer perceptron feed-forward networks and threshold decomposition has been presented in this thesis, which has been implemented using Turbo C++ language. Good results have been achieved by using program package. Results show that weight median filter based on threshold decomposition removes impulsive noise with an excellent image detail-preserving capability compared to nonlinear filter and linear filter. Restored images evaluation by using mean square error and speed. The package has been implemented using the MATLAB language. This study provides three types of filtering windows size, 3×3, 5×5 and 7×7 window size. The result shows that the mean square error of weight median filter based on threshold decomposition using 3×3 filtering window is less than 5×5, and 7×7 filtering window and the speed of weight median filter based on threshold decomposition using 3×3 is faster than 5×5, and 7×7 filtering window.